Job satisfaction and its relationship to enjoying life among primary school teachers in Basra Governorate (Journal of Misan Researches, 2020)
The current research seeks to identify the statistically significant relationship between job satisfaction and enjoyment of life among primary school teachers.In order to achieve the objectives of the current research, the researcher followed the steps of the relational descriptive approach. The research community has been identified for all primary school teachers in Basra Governorate. As for the research sample, it consisted of (200) male and female teachers.In order to collect data and information, the researcher prepared the current research tools and extracted the psychometric properties of them from the truth and reliability.After being satisfied with the research tools, they were applied to the research sample, and a set of results were reached, including:There is a high level of job satisfaction among primary school teachers in Basra GovernorateThere is a high level of enjoyment of life among primary school teachers in Basra Governorate 3-There is a statistically significant relationship between job satisfaction and enjoyment of life among primary school teachers in Basra Governorate